2011
DOI: 10.1111/j.1365-294x.2011.05308.x
|View full text |Cite
|
Sign up to set email alerts
|

Joint analysis of demography and selection in population genetics: where do we stand and where could we go?

Abstract: Teasing apart the effects of selection and demography on genetic polymorphism remains one of the major challenges in the analysis of population genomic data. The traditional approach has been to assume that demography would leave a genome-wide signature, whereas the effect of selection would be local. In the light of recent genomic surveys of sequence polymorphism, several authors have argued that this approach is questionable based on the evidence of the pervasive role of positive selection and that new appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
140
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 90 publications
1
140
0
Order By: Relevance
“…Patterns of genetic variation and population structure reflect past demographic processes [26], and genome-wide SNPs generated from ddRADseq provided enough information to distinguish recent demographic events from past geological processes. Our demographic models estimated divergence times and migration patterns that are consistent with the known geological and historical record of NYC.…”
Section: Resultsmentioning
confidence: 99%
“…Patterns of genetic variation and population structure reflect past demographic processes [26], and genome-wide SNPs generated from ddRADseq provided enough information to distinguish recent demographic events from past geological processes. Our demographic models estimated divergence times and migration patterns that are consistent with the known geological and historical record of NYC.…”
Section: Resultsmentioning
confidence: 99%
“…We then tested for clinal variation in gene expression in a subset of the genes for which clinal variation was detected for SNP allele frequencies. This study offers a clear illustration of the interplay between demographic history and selection in shaping genetic variation and of the intrinsic difficulty in telling the two apart (Li et al 2012). …”
mentioning
confidence: 99%
“…However, it is always difficult to distinguish these footprints from the confounding signatures of demography, such as population size expansion and bottleneck [93,94]. According to our work, the most reliable approach to detect selection, besides functional analysis, may be a genome-wide approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, it would be a great challenge for all who are working in this field to develop such tests. Recently, the (joint) analysis of demography and selection [25,26,42,90,93,99,100] has become an central issue, and it is believed that we are on the right track. However, researchers should be made aware that simulations have shown that the popularly used SweepFinder is not robust to certain demographics, for example, severe and recent bottlenecks [23].…”
Section: Discussionmentioning
confidence: 99%